Impact of contact on adolescents' mental health literacy and stigma: the SchoolSpace cluster randomised controlled trial. Issue 2 (19th February 2016) - Chisholm, Katharine; Patterson, Paul; Torgerson, Carole; Turner, Erin; Jenkinson, David; Birchwood, Max
Abstract : Objectives: To investigate whether intergroup contact in addition to education is more effective than education alone in reducing stigma of mental illness in adolescents. Design: A pragmatic cluster randomised controlled trial compared education alone with education plus contact. Blocking was used to randomly stratify classes within schools to condition. Random allocation was concealed, generated by a computer algorithm, and undertaken after pretest. Data was collected at pretest and 2-week follow-up. Analyses use an intention-to-treat basis. Setting: Secondary schools in Birmingham, UK. Participants: The parents and guardians of all students in year 8 (age 12–13 years) were approached to take part. Interventions: A 1-day educational programme in each school led by mental health professional staff. Students in the 'contact' condition received an interactive session with a young person with lived experience of mental illness. Outcomes: The primary outcome was students' attitudinal stigma of mental illness. Secondary outcomes included knowledge-based stigma, mental health literacy, emotional well-being and resilience, and help-seeking attitudes. Results: Participants were recruited between 1 May 2011 and 30 April 2012. 769 participants completed the pretest and were randomised to condition. 657 (85%) provided follow-up data. At 2-week follow-up, attitudinal stigma improved in both conditions with no significant effect of condition (95% CI −0.40 to 0.22, p=0.5, d=0.01). Significant improvements were found in the education-alone condition compared with the contact and education condition for the secondary outcomes of knowledge-based stigma, mental health literacy, emotional well-being and resilience, and help-seeking attitudes. Conclusions: Contact was found to reduce the impact of the intervention for a number of outcomes. Caution is advised before employing intergroup contact with younger student age groups. The education intervention appeared to be successful in reducing stigma, promoting mental health knowledge, and increasing mental health literacy, as well as improving emotional well-being and resilience. A larger trial is needed to confirm these results. Trial registration number: ISRCTN07406026; Results.